2022
DOI: 10.1111/1365-2745.13900
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity improves resistance of plant biomass and soil microbial communities to drought

Abstract: 1. Biodiversity is known to affect ecosystem resistance and have implications for the maintenance of ecosystem functions and services under climate change.Compared to numbers of studies focusing on above-ground vegetation, the response of below-ground communities to abiotic stresses along plant diversity gradients is often ignored and is considered an important knowledge gap in ecosystem ecology. Here we conducted an integrative research to evaluate the resistance of plant biomass, and soil microbial communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 145 publications
3
5
0
Order By: Relevance
“…Changes in fungal community diversity result from fungal redistribution, water use ( Barnard et al, 2013 ), or mycelial contraction ( Hossain et al, 2007 ), leading the community to adopt ecological strategies appropriate to different drought conditions. Our study found that BGB significantly affected fungal diversity ( Figure 4 ), which is consistent with the results of previous studies ( Li et al, 2022b ). This result may be attributed to two aspects.…”
Section: Discussionsupporting
confidence: 93%
“…Changes in fungal community diversity result from fungal redistribution, water use ( Barnard et al, 2013 ), or mycelial contraction ( Hossain et al, 2007 ), leading the community to adopt ecological strategies appropriate to different drought conditions. Our study found that BGB significantly affected fungal diversity ( Figure 4 ), which is consistent with the results of previous studies ( Li et al, 2022b ). This result may be attributed to two aspects.…”
Section: Discussionsupporting
confidence: 93%
“…Plant diversity has been shown to impact soil physicochemical properties and the soil microbial community via differences in root biomass, the quantity and quality of rhizodeposits and litter inputs, as well as changes in plant nutrient uptake and water use (Eisenhauer et al, 2017;El Moujahid et al, 2017;Orwin & Wardle, 2005). In line with expectations, we found that plant diversity had a significant effect on most of the biotic and abiotic soil variables that were recorded under ambient conditions; the only exceptions were total Li et al, 2022). Tighter linkages between fungi and plant roots and the extension of fungal mycelia from roots into soil may explain the results obtained here for fungal and bacterial Shannon diversity metrics (Yang et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…Although positive effects of plant diversity have previously been reported for some attributes of microbial performance under drought (e.g. cell counts, hyphal length, AMF infection rates, Bennett et al, 2020), as well as for microbial community structure (Li et al, 2022), other grassland studies of ‘diversity × drought’ interactions on microbial biomass have generated mixed results (Thakur et al, 2015). Divergent results among studies likely reflect variation in drought treatments and soil properties across the different experiments, as well as variable responses of root exudation to drought (Preece & Peñuelas, 2016); abiotic soil properties such as pH, C, nutrient availability and/or stoichiometry have the potential to mediate microbial responses to environmental change, either by shaping the intrinsic attributes of soil microbial communities that confer resistance or by buffering the impact of the environmental disturbance itself on the soil microbial community (Bardgett & Caruso, 2020; Griffiths & Philippot, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a low drought resistance could be observed in response to elevated N deposition, suggesting that ecosystem responses to precipitation changes may be related to N levels. Moreover, plant diversity in a grassland ecosystem can enhance the resistance of plant biomass and soil microbial communities to drought (Li et al., 2022), implying that both plant and soil microbial communities might be involved in responses to precipitation changes under conditions of N enrichment (Li et al., 2022; Ochoa‐Hueso, 2016; Valliere et al., 2017).…”
Section: Introductionmentioning
confidence: 99%